Engrang batok: The influence of games on children's social development at Miftahul Jannah Kindergarten, South Aceh - Ulvia, Rauzatul; Muthmainnah, Muthmainnah; Amelia, Lina; Munafiah, Nida'aul (Universitas Islam Negeri Raden Intan Lampung, 2024)
Background: Social relationships are a development that has an urgency to form good interactions from an early age. However, it was found that children at Miftahul Jannah Kindergarten in South Aceh still had difficulty making friends with their peers, often being alone and not gathering together.Aim: Therefore, the engrang batok game aims to determine its effect on children's social relationships in kindergarten.Method: This quantitative research with a pre-experimental design uses a one group pretest and posttest approach. The research sample consisted of 15 children from class A using a total sampling technique. Data was obtained through observation sheets and documentation and then analyzed using the SPSS 20 application to determine normality tests and hypothesis tests.Results: The results showed that the normality test had a normal distribution, the t-test calculation had a value of 15.94, and the t-table had a value of 1.761. Based on these results, it can be said that Tcount > Ttable means that Ha is accepted and Ho is rejected.Conclusion: Therefore, it can be concluded that the engrang batok game can influence the development of children's social relationships at Miftahul Jannah Kindergarten, South Aceh.